Electronic and Magnetic Structure of LaSr-2×4 Manganese Oxide Molecular Sieve Nanowires. (16th April 2014) - Gazquez, Jaume; Carretero-Genevrier, Adrián; Gich, Martí; Mestres, Narcís; Varela, María
Abstract In this study we combine scanning transmission electron microscopy, electron energy loss spectroscopy and electron magnetic circular dichroism to get new insights into the electronic and magnetic structure of LaSr-2×4 manganese oxide molecular sieve nanowires integrated on a silicon substrate. These nanowires exhibit ferromagnetism with strongly enhanced Curie temperature (Tc>500 K), and we show that the new crystallographic structure of these LaSr-2×4 nanowires involves spin orbital coupling and a mixed-valence Mn3+/Mn4+, which is a must for ferromagnetic ordering to appear, in line with the standard double exchange explanation.